2016
DOI: 10.1186/s13063-016-1559-y
|View full text |Cite
|
Sign up to set email alerts
|

The Stroke and Carer Optimal Health Program (SCOHP) to enhance psychosocial health: study protocol for a randomized controlled trial

Abstract: BackgroundStroke is a leading cause of disability and distress, and often profoundly affects the quality of life of stroke survivors and their carers. With the support of carers, many stroke survivors are returning to live in the community despite the presence of disability and ongoing challenges. The sudden and catastrophic changes caused by stroke affects the mental, emotional and social health of both stroke survivors and carers. The aim of this study is to evaluate a Stroke and Carer Optimal Health Program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Literature reviews and research protocols were conserved up to this stage so that author tracing and examination of reference lists could also be undertaken. The same five databases were used to trace the authors of two study protocols (Brasier et al, 2016;Terrill et al, 2016) but did not uncover additional studies; nor did an examination of reference lists of one literature review, and these articles were then dropped.…”
Section: Study Selectionmentioning
confidence: 99%
“…Literature reviews and research protocols were conserved up to this stage so that author tracing and examination of reference lists could also be undertaken. The same five databases were used to trace the authors of two study protocols (Brasier et al, 2016;Terrill et al, 2016) but did not uncover additional studies; nor did an examination of reference lists of one literature review, and these articles were then dropped.…”
Section: Study Selectionmentioning
confidence: 99%
“…To our knowledge, this the first full economic evaluations of self-management intervention for post stroke patients. Although the importance was recognised [9,35] and ongoing studies are identified [36][37][38][39], no economic evaluation relating to this topic was published yet. The USER-Participation scores were significant different between the two groups, this does not account for UPCC, Utilities and QALYs.…”
Section: Discussionmentioning
confidence: 99%
“…Written informed consent from each participant was obtained. The study protocol is reported elsewhere; 33 there were no significant deviations from this.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to usual stroke care, 33 the intervention group received a program of personalized psychosocial support -Stroke Care Optimal Health Program (SCOHP) -delivered over 8 onehour weekly sessions, followed by a 'booster' session at three months (Table 1). Participants received a structured workbook and professional facilitator (psychologist) who worked with them on an individualized basis and offered flexible delivery times (weekend, afterhours) and modes (face-to-face, telephone, Skype).…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation